FABRICATION AND CHARACTERIZATION OF AL7075-TITANIUM CARBIDE/GRAPHITE COMPOSITES FOR ENCHANCED MECHANICAL PROPERTIES USING FSP - Yang, Xiong Liang (IRC, 2021)
Friction Stir Processing (FSP) is a solid-state surface processing that is used for modification and enhancement of microstructure and mechanical properties.